Development and validation of a real-time PCR assay, and phylogenetic analysis of Anaplasma platys - (:unkn) unknown (My University, 2025)
Anaplasmosis is a tick-borne disease caused by species of the genus Anaplasma. In dogs anaplasmosis is caused by Anaplasma phagocytophilum and Anaplasma platys. These bacteria are in the family Anaplasmataceae in the order Rickettsiales. Anaplasma platys is a Gram-negative bacterium that is of public health and veterinary importance. This pathogen exclusively infects platelets and causes infectious cyclic thrombocytopenia in dogs. Infection occurs through the bite of an infected ixodid tick, Rhipicephalus sanguineus, which is the principal vector and is also known to transmit Ehrlichia canis, another bacteria of veterinary importance. Our group recently reported on the developed group-specific Ehrlichia/Anaplasma primers and the A. platys-specific TaqMan® Minor Groove Binder probe for multiplexing purposes. This study validated the A. platys TaqMan® PCR assay targeting the 16S rRNA gene. Furthermore, phylogenetic analysis was used to characterize A. platys. The assay efficiency was 94.9 %, and the 95 % limit of detection (LOD) was 5.08 A. platys plasmid copies/μl blood with a 95 % confidence interval of 3.1–10.2. The assay did not cross-react when tested against other haemoparasites. The phylogenetic characterization of the Mnisi community samples revealed that the A. platys sequences from this area grouped with other A. platys sequences from South Africa and other countries, including India, Zambia, Taiwan, Thailand, and Croatia. The developed TaqMan® qPCR assay will be a valuable tool for the early diagnosis of A. platys by preventing inappropriate use of antibiotics and alleviating potential emerging antimicrobial resistance. Additionally, early detection and administration of the correct antibiotics speed recovery time.
Keywords: African Research